Life Pharmacy Website Design with Model View Controller Method - Dapit Indra (Bahasa Indonesia, 2020)
Nowadays research and development of medicinal plants both at home and abroad is growing rapidly. Research is mainly developing in terms of pharmacology and phytochemicals based on indications of medicinal plants that have been used by some people with empirically proven efficacy. The results of this study, of course, further strengthen the users of medicinal plants for their efficacy and usefulness. Moreover, many researchers have also conducted toxicological tests to determine the safety of medicinal plants that are often used for long-term use, as well as incidental use. The traditional healers also have a lot of knowledge of poisonous medicinal plants, but still use them because they know how to process them.